Application Experience and Patient Feedback Analysis of 3D Printed AFO with Different Materials: A Random Crossover Study. (14th June 2021) - Meng, Xianzhong; Ren, Min; Zhuang, Yan; Qu, Yu; Jiang, Linling; Li, Zhenjing
Abstract : Purpose . This study is aimed at analyzing the application experience and feedback of the patients with poststroke ankle dorsiflexion disorders for 3D printed AFO with three different materials. Methods . 15 patients were randomly divided into three groups; 3D printed AFO with 3 different materials (PA2200, Somos NeXt, and PA12) was used to each group, according to the crossover study design, in order to ask the three groups of patients to use three different materials of 3D printed AFO. Assessment was taken by the end of each test round. Through statistical processing, the patient feedback data of the three groups of materials of 3D printed AFO were obtained. Results . In the material comfort assessment of the AFO, Somos NeXt was compared with PA2200, and the p value was <0.05; in the item of surface smoothness of the AFO, Somos NeXt was compared with PA2200, and the p value was <0.01; at the same time, PA12 was compared with PA2200, and the p value was <0.05. Conclusion . The 3 different materials of 3D printing AFO bring different experience, and we also have sufficient reason to believe that there will be differences in the auxiliary effect of this on patients, which leads the patient's selection too. The material Somos NeXt is much popular and has certain clinical advantages.